The mystery "Well": A natural cloud chamber?. (March 2015) - Hovorka, Jan; Holub, Robert F.; Zdimal, Vladimir; Bendl, Jan; Hopke, Philip K.
Abstract: A serendipitous discovery was made of a cistern in the eastern Czech Republic that periodically has water droplets falling on the surface of the water when there is no ambient precipitation occurring. Measurements of temperature, humidity, droplet size and other related parameters have been made to try to understand what is inducing the droplet formation. It appears that this system represents an unintentional cloud chamber.